C1GALT1 Seems to Promote In Vitro Disease Progression in Ovarian Cancer. Issue 5 (June 2017) - Chou, Chih-Hsing; Huang, Miao-Juei; Liao, Ying-Yu; Chen, Chi-Hau; Huang, Min-Chuan
Abstract : Objective: Aberrant glycosylation affects many cellular properties in cancers. The core 1 β1, 3-galactosyltransferase (C1GALT1), an enzyme that controls the formation of mucin-type O -glycans, has been reported to regulate hepatocellular and mammary carcinogenesis. This study aimed to explore the role of C1GALT1 in ovarian cancer. Methods: C1GALT1 expression was assessed in a public database based on microarray data from 1287 ovarian cancer patients and ovarian cancerous tissues. Lectin blotting and flow cytometry analysis were conducted to detect changes in O -glycans on ovarian cancer cells. Effects of C1GALT1 on cell growth, migration, and sphere formation were analyzed in C1GALT1 knockdown or overexpressing ovarian cancer cells in vitro. Expression of cancer stemness-related genes was analyzed by quantitative reverse transcription polymerase chain reaction. Results: High C1GALT1 expression shows a trend toward association with poor survival in ovarian cancer patients. C1GALT1 modifies O -glycan expression on surfaces and glycoproteins of ovarian cancer cells. Knockdown of C1GALT1 decreased cell growth, migration, and sphere formation of ES-2 and OVTW59-p4 cells. Conversely, overexpression of C1GALT1 promoted such malignant properties of SKOV3 cells. Furthermore, C1GALT1 regulated the expression of several cancer stemness-related genes, including CD133, CD24, Oct4, Nanog, and SNAI2, in ovarian cancer cells. Conclusions: C1GALT1 modifies O -glycan expression and enhances malignant behaviors in ovarian cancer cells, suggesting that C1GALT1 plays a role in the pathogenesis of ovarian cancer and targeting C1GALT1 could be a promising approach for ovarian cancer therapy. Abstract : Supplemental digital content is available in the text.